2023
DOI: 10.3390/ijms24043212
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Is Involved in Physiologic Cardiac Hypertrophy of Mice via the p38 Signaling Pathway after Voluntary Running

Abstract: Appropriate exercise such as voluntary wheel-running can induce physiological cardiac hypertrophy. Notch1 plays an important role in cardiac hypertrophy; however, the experimental results are inconsistent. In this experiment, we aimed to explore the role of Notch1 in physiological cardiac hypertrophy. Twenty-nine adult male mice were randomly divided into a Notch1 heterozygous deficient control (Notch1+/− CON) group, a Notch1 heterozygous deficient running (Notch1+/− RUN) group, a wild type control (WT CON) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It is also possible that a dose-dependent increase in cardiac hypertrophy was seen, where the larger volume of training done by EAP mice elicited greater hypertrophy. While this is possible, other studies have shown significant cardiac hypertrophy in a period of 2 weeks 37 . During the weeks 5 and 6 of our study, here was not a significantly different distance ran by EAP and LAP mice, suggesting that an equal exercise stimulus occurred for the final 2 weeks.…”
Section: Discussionmentioning
confidence: 85%
“…It is also possible that a dose-dependent increase in cardiac hypertrophy was seen, where the larger volume of training done by EAP mice elicited greater hypertrophy. While this is possible, other studies have shown significant cardiac hypertrophy in a period of 2 weeks 37 . During the weeks 5 and 6 of our study, here was not a significantly different distance ran by EAP and LAP mice, suggesting that an equal exercise stimulus occurred for the final 2 weeks.…”
Section: Discussionmentioning
confidence: 85%
“…6d and Supplementary Table S3), identifying five related pathways. Of these, pathways 1 and 3 are related to the Notch1 gene, further highlighting Notch1's essential role in embryonic development and heart formation and its role as a crucial factor in the proliferation and differentiation of cardiac stem cells [31]. Inhibition of Notch1 signaling could lead to life-threatening dilated cardiomyopathy, emphasizing that scKEPLM can not only validate known disease-related genes and pathways but also expand our perspectives in researching cardiac disease biomarkers and therapeutic targets.…”
Section: Insights Into Disease Marker Genes By Sckeplmmentioning
confidence: 99%